Identifikasi Faktor-Faktor Yang Mempengaruhi Motivasi Belajar Mahasiswa Pada Program Studi S1 Pendidikan Ekonomi Angkatan 2015 Fakultas Ekonomi Universitas Negeri Gorontalo - Israfani Logiswara Lagili; Usman Moonti; Melizubaida Mahmud (universitas negeri gorontalo, 2019)
This research aims to identification of factors that influencethe motivation of student learning on the study program S1Economic Education, batch of 2015,Faculty of Economics,State University of Gorontalo. By Knowing the factors thatinfluence the motivation to learn can provide useful informationin teaching and learning process. The date in thisstudy was obtained by distributing questionnaires to studentsof Economics Education , batch of 2015 Faculty of Economics,State University of Gorontalo, therefore , the data of thisresearch are primary data.The analytical teachnique used is Factor Analysis. The resultof factor analysis shows that the most influential aspect towardstudents learning motivation is physiology of 93,4%.The next factor that influences is the desire to gain recognition/recognition 87,2%, and social relationships with friends80,6%. While the lowest aspect that affesct the studentslearning motivation sense of security in learning 75,8% andthe desire to self-actualization by 75%.